Virome Status of Preclonal Candidates of Grapevine Varieties (Vitis vinifera L.) From the Slovenian Wine-Growing Region Primorska as Determined by High-Throughput Sequencing - Miljanić, Vanja; Jakše, Jernej; Kunej, Urban; Rusjan, Denis; Škvarč, Andreja; Štajner, Nataša (Frontiers in Microbiology, 2022)
Diseases caused by viruses and virus-like organisms are one of the major problems in viticulture and grapevine marketing worldwide. Therefore, rapid and accurate diagnosis and identification is crucial. In this study, we used HTS of virus- and viroid-derived small RNAs to determine the virome status of Slovenian preclonal candidates of autochthonous and local grapevine varieties (Vitis vinifera L.). The method applied to the studied vines revealed the presence of nine viruses and two viroids. All viral entities were validated and more than 160 Sanger sequences were generated and deposited in NCBI. In addition, a complete description into the co-infections in each plant studied was obtained. No vine was found to be virus- and viroid-free, and no vine was found to be infected with only one virus or viroid, while the highest number of viral entities in a plant was eight.